Fracture Patella - Outcome of Early Movement of Knee After Stable Fixation (Journal of Armed Forces Medical College, Bangladesh, 2009)
The study was carried out at Combined Military Hospitals of Jessore and Dhaka over a period of three and half years. The aim of this study was to evaluate the functional status of the knee joint by allowing early knee movement after stable fixation of fracture patella in 18 patients. The commonest age group involved in fracture patella was at the fourth and fifth decade (66.66 %). Road traffic accident (RTA) and domestic injuries like fall in the slippery ground were the major causes of fracture and the incidences were similar (44.44%). Stable fixation was achieved by applying modified tension band wiring in 7 patients but remaining 11 patients required additional cerclage wiring. Postoperatively (within 48 to 72 hours) when the pain was tolerable, assisted active movement of the knee was started. Subsequently assisted active, active and passive movement of knee along with quadriceps exercise was continued. The functional status of the knee was assessed according to a predecided subjective and objective evaluation chart. 13 patients (72.23%) found satisfactory (Excellent and good) in subjective evaluation and 16 (88.89%) in objective evaluation. One patient who did not follow the post operative advice adequately, developed more than 2 mm displacement at the fracture site and about 25° extension lag. It has been revealed that initiating early postoperative knee movement after stable fixation of fracture patella could prevent stiffness of knee and thereby confers better function. Key Words: Fracture patella, Early movement, Stable fixation.   doi: 10.3329/jafmc.v5i1.2843 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.11-13